Behavior of Axially Loaded Concrete Columns Reinforced with Steel Tubes Infilled with Cementitious Grouting Material - Ahlam A. Abbood; Nazar Oukaili (Salehan Institute of Higher Education, 2024)
The paper presents a novel method of reinforcing concrete columns using small-diameter steel tubes instead of traditional steel bars. The researchers conducted experimental investigations on twelve mid-scale circular concrete column specimens, which were divided into two groups consisting of six specimens each: short and long columns. Two of the specimens in each group were reinforced with steel bars, while the remaining four were reinforced with steel tubes filled with cementitious grouting material. The study proposed two concepts for cementitious grouted steel-tube reinforcement. The first concept utilized steel tubes with equivalent net areas to the steel bar areas used in the reference column, while the second concept used steel-tube reinforcement with the same diameter as the steel bars in the reference column. Nonlinear Finite Element (FE) analyses were conducted on experimental specimens using ABAQUS software. The results showed that using steel tubes with an area equivalent to that of steel bars instead of conventional columns increased the bearing capacity of reinforced concrete columns by 17%. Moreover, using steel tubes whose area matched 30% of the steel bar area achieved a bearing capacity of about 81% of the conventional concrete columns. The experimental and FE analysis findings indicate that this methodology can increase the bearing capacity of reinforced concrete columns when compared to traditional methods. The axial load-axial displacement curves, axial load-axial strain curves, and failure load of the FE model all demonstrated good convergence with the experimental data. Doi: 10.28991/CEJ-2024-010-02-017 Full Text: PDF